Patrimoine ferroviaire du xxe siècle : quelle reconnaissance et quelles adaptations pour sa conservation ? - Alexandrina Striffling-Marcu; Véronique Veston (In Situ)
What future for 20th century railway architectural heritage? This concern is about both the evolution of the heritage value assigned to railway architecture and the processes carried out today to preserve and renew this complex and pluralist heritage: the identification for the protection and environmental renewal of railway heritage conducted by AREP (“Aménagements Recherche Pôles d’échanges”, Planning, Research, Interchange hubs), “1001 gares” (1001 stations) programme of Gares & Connexions in France, “Stazioni impresenziate” (unstaffed station) programme of the RFI (Rete ferroviaria italiana) in Italy and “Activos para el desarrollo” (Assets for sustainable development) of ADIF in Spain. Its use and its evolution are major issues in the understanding of railway heritage and need to respond to changes in society. This article thus intends to take part in a theoretical - current doctoral research - and operational reflection - experience with the AREP company, subsidiary office of SNCF Gares & Connexions - on the recognition and optimisation of 20th-century railway heritage through the study of the measures developed in France, main object of the analysis, enriched with an international perspective with Spain and Italy. The first part will provide the state of the art concerning the variety of elements that constitute a transnational heritage common to several countries and their heritage value, then a second part will focus on the strategies developed in the three countries in order to make the status of the most emblematic buildings of this railway heritage evolve: railway stations.